Brightest path tracing: A Python package to trace the brightest path in 2D and 3D images - Jha, Vasudha; Cudmore, Robert H (bioRxiv, 2023)
Brightest path tracing is a widely used image processing technique in several fields including biology, geography, and geology. However, despite the availability of many image processing libraries in Python, few offer an out-of-the-box implementation of a brightest path tracing algorithm. This paper presents a Python package, brightest-path-lib, that efficiently finds the path with maximum brightness between points in a 2D or 3D image. An example graphical user interface is provided as a Napari plugin. Taken together, the package and plugin provide a powerful and extensible tool for users to efficiently trace structures of interest in 2D or 3D images, regardless of the type of structure being analyzed.